The Role of Brand Trust in Achiving Competitive Advantage (Case Study: PT Pos Indonesia Bandung) - Ani Solihat; Mimin Nurjanah; Rani Rahmayani; Andry Trijumansyah; Iis Iskandar (Relevance: Journal of Management and Business, 2020)
The purpose of this study is to determine the role of brand trust in achieving the competitive advantage of PT Pos Indonesia Bandung freight forwarding services. The method in this study uses quantitative methods. This research uses the Stastical Pakage for the Social Sciences (SPSS) program which aims to measure the effect of brand trust on the competitive advantage of PT Pos Indonesia Bandung freight forwarding services. The sampling technique of this study used purposive sampling and the determination of samples was calculated using the Rao Purba formula with a total sample of 96 people. The respondents of this study were users of freight forwarding services, especially PT Pos Indonesia and other freight forwarding services (TIKI, JNE, J&T, etc.). The design of this study uses descriptive and verification to assess the picture and influence between variables. The results of this study indicate that brand trust has a positive and significant effect on the competitive advantage of PT Pos Indonesia Bandung freight forwarding services.